Strength & Conditioning and swimming performance - Amaro, Nuno Miguel Pires Alves (2018)
The ability to apply force is crucial in competitive swimming, particularly in short distances. Accordingly, literature has shown that high values of upper-body strength and power are determinant to succeed in competitive swimming. Thus, dry-land Strength and Conditioning (S&C) is a common practice in swimming prescription in order to improve performance or prevent injuries. Nevertheless, research over the effects of S&C training in swimming performance is scarce and far from consensus. The main purpose of this thesis was to analyze the effect of S&C training programs on swimming performance in age group swimmers. Additionally, the reliability of tethered swimming evaluation with age group swimmers was verified, as a methodology to evaluate S&C training effects in swimming performance. For the accomplishment of these purposes the following sequence was used: (i) reviewing the available literature; (ii) examination of the reliability of tethered swimming evaluation; (iii) analyzing the effects of S&C programs in dry-land strength and swimming performance; (iv) proposing a practical S&C program to swimming prescription. The main conclusions drawn were: (i) there is limited research on S&C training effects in competitive swimming and the existent was mainly conducted with older and experienced swimmers; (ii) tethered swimming is a reliable test to evaluate force exerted in water by swimmers familiarized with the test; (iii) tethered swimming evaluations throughout the season may allow coaches to control swimmers’ ability to exert inwater force and evaluate the effects of S&C training programs, in age group swimmers; (iv) 6 weeks of a complementary S&C training allow improvements in dry-land strength, in age group swimmers; (v) a 4-week adaptation period is suggested to allow transferability of S&C improvements to swimming performance; (vi) explosiveness should be the goal of S&C training in order to allow swimming performance enhancement in short distance swimming, with age group swimmers. These findings can be used by coaches and researches as a starting point to future S&C training programs in age group swimmers.